Characterization of Mycobacterium tuberculosis var. africanum isolated from a patient with pulmonary tuberculosis in Brazil - Rabahi, Marcelo Fouad (2020)
Universidade Federal de Goi?s. Hospital das Cl?nicas. Goi?nia, GO, Brazil.